2004
DOI: 10.1097/01.nmd.0000146739.26187.15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Long Asylum Procedure on the Prevalence of Psychiatric Disorders in Iraqi Asylum Seekers in The Netherlands

Abstract: Clinically, a long asylum procedure seems to be associated with psychiatric disorders. However, data on this issue are lacking. In a national community-based study, using random sampling, we compared two groups of Iraqi asylum seekers, who had resided less than 6 months (N = 143) and more than 2 years (N= 151), respectively, in The Netherlands. Respondents were interviewed with fully structured, culturally validated, translated questionnaires. Psychiatric (DSM-IV) disorders were measured with the Composite Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
268
4
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(300 citation statements)
references
References 27 publications
15
268
4
13
Order By: Relevance
“…Increased psychiatric morbidity in asylum seekers has been confirmed in previous studies (12,22). The finding that refugees did not show elevated incidences of clinically relevant levels of anxiety fits well with the previously noted decline in psychopathological symptoms in asylum seekers after they have been accepted as refugees (23).…”
Section: Accepted M Manuscriptsupporting
confidence: 75%
See 1 more Smart Citation
“…Increased psychiatric morbidity in asylum seekers has been confirmed in previous studies (12,22). The finding that refugees did not show elevated incidences of clinically relevant levels of anxiety fits well with the previously noted decline in psychopathological symptoms in asylum seekers after they have been accepted as refugees (23).…”
Section: Accepted M Manuscriptsupporting
confidence: 75%
“…Asylum seekers and refugees in particular were found to suffer from symptoms of posttraumatic stress, depression and anxiety (e.g. 8,12,22). Several studies report associations of psychopathology not only with traumatic experiences prior to migration but also with the living situation in exile (13,20,22).…”
Section: Introductionmentioning
confidence: 99%
“…When the study Refugee children from the Middle East was carried out, the existing knowledge regarding the association between asylum seeking and mental health was limited. Subsequently, repeated studies of adult asylum seekers have suggested an association between refugee status and asylum seeking and poor mental health (96)(97)(98)(99)(100)(101)(102)(103)(104)(105). In addition, later studies have confirmed that asylum-seeking children suffer from poor mental health as well; for instance, 58% of the 11-16-year-old asylum seekers in Denmark were found to have signs of a mental illness (106) according to a combination of information from teachers and the children themselves.…”
Section: Mental Health In Young Refugeesmentioning
confidence: 99%
“…Comorbidity of PCBD and/or PTSD with other psychiatric disorders such as major depressive disorder (MDD) (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995; Schaal, Dusingizemungu, Jacob, Neuner, & Elbert, 2012), psychotic disorders (Sareen, Cox, Goodwin, & Asmundson, 2005) and substance abuse disorders (Kessler et al, 1995) is often observed. Furthermore, refugees are confronted with ongoing stressors that can fuel the risk for psychopathology (Laban 2004, 2005), such as insecurity about residential status, concerns about wellbeing of family members left behind, socioeconomic disadvantage, and adaptation to the host culture.…”
mentioning
confidence: 99%